Pengaruh Media Sosial Terhadap Minat Beli Konsumen SNB Coffee Lamongan - Rangga Arya Dhaniswara; Nirma Kurriwati (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study wants to find out how much influence social media has on consumer buying interest at SNB Coffee Lamongan. Using samples obtained from questionnaires to 50 respondents. The data is processed using quantitative methods with tests, namely T test, validity test, reliability test, and normality test, which will be analyzed using simple regression, with the help of SPSS software.The results obtained in this study are that social media (X) has a positive and significant effect on Consumer Buying Interest (Y) at SNB Coffee Lamongan